Sideshow: Providing Peripheral Awareness of Important Information - Cadiz, JJ; Venolia, Gina; Jancke, Gavin; Gupta, Anoop (2001)
A fundamental issue with user interfaces is how to help users stay aware of information without being overly intrusive or distracting. In this paper we describe Sideshow, a peripheral awareness interface designed to help users stay aware of people and information. We present data from a field trial of Sideshow where several hundred employees within our company used Sideshow over a seven-month period of time. The data indicate that Sideshow’s design accomplishes the goal of providing awareness of important information without being overly distracting.